Paratexts in English printed drama to 1642 - Berger, Thomas L (Cambridge university, 2014)
Includes bibliographical references, finding list, and indexes; Volume 1. Single-text and collected editions to 1623 -- volume 2. Single-text and collected editions, 1624-1642